Peran Komunikasi Dalam Pembentukan Iklim Organisasi Pada Kelompok Tani Kopi Wanoja di Desa Ibun Bandung - Retno Kurnia Muktiarum (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2026)
Communication plays an important role in shaping organizational climate because it influences interaction, trust, and collaboration among organizational members. However, studies on communication practices in community-based organizations, particularly farmer groups, remain limited compared to formal organizations. This study aims to analyze the role of communication in shaping the organizational climate of the Wanoja Coffee Farmers Group in Ibun Village, Bandung Regency. This research employed a qualitative descriptive-exploratory approach. Data were collected through in-depth interviews, non-participant observation, and documentation involving the group leader and active members. The findings show that communication within the Wanoja Coffee Farmers Group is conducted through open, participatory, and supportive practices that strengthen trust, member involvement, collective decision-making, and organizational cohesion. The study also reveals that communicative leadership, regular evaluation forums, and family-oriented relationships contribute to the development of a healthy organizational climate. This study implies that effective communication practices can serve as a strategic foundation for strengthening sustainability and collaboration in community-based organizations.